Evaluation of The Maternal Delivery Care Program for Pregnant Women at Mokoau Health Center, Kendari City - Hartati Bahar (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Maternal and child health plays a vital role in determining the quality of life and overall well-being of a nation. Health facilities serve a crucial role as accessible providers of medical services for pregnant women and infants, ensuring timely and high-quality care. Given the importance of improving maternal and child health, the support of health workers and active community participation are essential components. Objective: This study aims to evaluate the childbirth program for pregnant women in the working area of Mokoau Health Center in Kendari City, focusing on the program’s input, process, and output components. Methods: This study employed a qualitative approach. Six informants were involved, consisting of a midwife, a health promotion officer, two posyandu cadres, and two pregnant women. Informants were selected using purposive sampling based on their involvement in the implementation of the childbirth program and their relevant knowledge of the service process. Data were collected through in-depth interviews and analyzed using content analysis. Results: The findings indicate that all stakeholders play an active role in implementing the childbirth program at Mokoau Health Center, from service provision to health education for pregnant women. Various services and facilities are available, ranging from initial pregnancy examinations at the posyandu to the delivery process. However, several barriers were identified, including limited family support, low maternal awareness, and difficult access to health facilities. The availability of the national health insurance (BPJS) greatly contributes to increasing the coverage of facility-based deliveries. Pregnant women in the Mokoau area also reported significant benefits from giving birth at health facilities. Conclusion: The childbirth program at Mokoau Health Center operates through collaboration among health workers, cadres, and families. Although several challenges persist during its implementation, a number of supporting factors continue to sustain and strengthen the program in the area. Keywords: Delivery Birth, Pregnant Women, Health Center